Connect with your Users: Usability Testing and How User Experience May Actually Work for You - Webb, Kathryn Kavanagh; Rhodes, Tamara (My University, 2016)
For a library, User Experience (UX) refers to studying the emotions and attitudes of its users regarding the library building, website, or services. This can be executed through usability testing, which allows you to truly learn how users experience the library in all its forms. In this poster, a library system conducted a pilot project, a usability test, to research optimal staffing configurations with the goal of developing a sustainable UX strategy. A task force identified and tested a webpage common to both libraries in the two-library system - the Database List. Faculty and student users were tested and recorded as they completed various tasks using the original Database List and then subsequent redesigned versions. As a result of the study, the Database List was redesigned, personas - fictional characters of users created from actual user data- were developed, and the task force submitted recommendations for the best staffing model for sustainable UX. The presenters will outline the methods and tools used for the usability study, with the benefits and drawbacks of the different staffing models, and exhibit the findings of the project. This poster is a must-see for anyone who is interested in the best way to implement UX in their library.
Keywords: user experience; usability testing; libraries; staffing